2000
DOI: 10.1016/s0002-9440(10)64851-1
|View full text |Cite
|
Sign up to set email alerts
|

Different Subtypes of Human Lung Adenocarcinoma Caused by Different Etiological Factors

Abstract: Human lung adenocarcinomas are only relatively weakly associated with tobacco smoke, and other etiological factors need to be clarified. These may also vary with the histopathology. Because the p53 mutation status (frequency and spectrum) of a carcinoma can provide clues to causative agents, we subclassified 113 adenocarcinomas into five cell types: hobnail, columnar/cuboidal, mixed, polygonal, and goblet (54, 23, 18, 13, and 5, respectively) and investigated relationships with p53 mutations and smoking histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 34 publications
(22 reference statements)
1
51
0
1
Order By: Relevance
“…These findings are consistent with Lynch et al (2004), Kosaka et al (2004), and Marchetti et al (2005). Adenocarcinomas that develop in nonsmokers frequently display features of BAC and papillary type tumours, whereas those that develop in smokers frequently include poorly differentiated and solid subtype tumours (Hashimoto et al, 2000;Yang et al, 2002;Nordquist et al, 2004). High incidence of harbouring EGFR mutations in nonsmokers adenocarcinoma well-explains this predilection on pathological findings.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings are consistent with Lynch et al (2004), Kosaka et al (2004), and Marchetti et al (2005). Adenocarcinomas that develop in nonsmokers frequently display features of BAC and papillary type tumours, whereas those that develop in smokers frequently include poorly differentiated and solid subtype tumours (Hashimoto et al, 2000;Yang et al, 2002;Nordquist et al, 2004). High incidence of harbouring EGFR mutations in nonsmokers adenocarcinoma well-explains this predilection on pathological findings.…”
Section: Discussionsupporting
confidence: 82%
“…However, lung cancer also develops in nonsmokers, and 30 -40% of the lung cancer patients in Japan have never smoked history are female, and their major histological tumour type is adenocarcinoma (Sobue et al, 1994;Akazawa et al, 2003). While several reports have shown that the adenocarcinomas that occurred in nonsmokers were distinct from those that developed in smokers in terms of their histological subclassification, prognosis, gene expression pattern, and gene alterations (Tsuchiya et al, 1988;Hashimoto et al, 2000;Ahrendt et al, 2001;Bhattacharjee et al, 2001;Koga et al, 2001;Noda et al, 2001;Vahakangas et al, 2001;Yang et al, 2002), few significant genetic alterations have been reported in adenocarcinomas that developed in nonsmokers.…”
mentioning
confidence: 99%
“…In addition, they often featured mucin production, as proven by Alcian Blue staining (Figure 1b) with acinar structures. As for the cell types originally proposed by Hashimoto et al, 18 the columnar cell type was characteristic of EML4-ALK lung cancers ( Figure 1). …”
Section: Dna Extraction and Mutation Analysis Of Egfr Kras And Tp53mentioning
confidence: 64%
“…17 Mutation analysis of TP53 was also performed as described earlier. 18 Genomic DNAs from fresh tumor samples were prepared and exons 4-8 and 10 of the TP53 gene were analyzed by the PCR -single-strand conformation polymorphism and DNA sequencing. For case #4808, TP53 mutation analysis was performed using DNA extracted from formalin-fixed paraffin-embedded tissue and a method based on direct sequencing, because no fresh sample was available for this study at the time of the current study.…”
Section: Dna Extraction and Mutation Analysis Of Egfr Kras And Tp53mentioning
confidence: 99%
“…In the present study, therefore, we focused specifically on recurrence of stage I adenocarcinomas that had been completely resected, and followed the outcome of the patients over a 5-year period. The histology of the adenocarcinoma was also further restricted to the well differentiated type with a hobnail cell morphology, which is the most common cell type of this tumor (11). It was expected that the results would help to clarify the changes in protein function that induce micro-metastasis in early-stage NSCLC, and indicate possible new avenues for the development of drugs to suppress tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%